2016
DOI: 10.1038/srep25491
|View full text |Cite|
|
Sign up to set email alerts
|

Characterization of anti-leukemia components from Indigo naturalis using comprehensive two-dimensional K562/cell membrane chromatography and in silico target identification

Abstract: Traditional Chinese Medicine (TCM) has been developed for thousands of years and has formed an integrated theoretical system based on a large amount of clinical practice. However, essential ingredients in TCM herbs have not been fully identified, and their precise mechanisms and targets are not elucidated. In this study, a new strategy combining comprehensive two-dimensional K562/cell membrane chromatographic system and in silico target identification was established to characterize active components from Indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 48 publications
3
28
0
Order By: Relevance
“…Therefore, it was first examined whether the growth inhibitory effect of isorhamnetin in Hep3B cells was associated with cell cycle arrest. The results of flow cytometry analysis showed that isorhamnetin caused G2/M phase arrest, similar to the results of previous studies in several human cancer cell lines (Li et al 2014;Wu et al 2016;Wei et al 2018;Zhang et al 2018), suggesting that G2/M arrest is one of the mechanisms of isorhamnetin-mediated growth inhibitory effect in Hep3B cells. The progression of the cell cycle in eukaryotic cells is strictly controlled by the interaction of cyclins and Cdks with their inhibitory factors.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Therefore, it was first examined whether the growth inhibitory effect of isorhamnetin in Hep3B cells was associated with cell cycle arrest. The results of flow cytometry analysis showed that isorhamnetin caused G2/M phase arrest, similar to the results of previous studies in several human cancer cell lines (Li et al 2014;Wu et al 2016;Wei et al 2018;Zhang et al 2018), suggesting that G2/M arrest is one of the mechanisms of isorhamnetin-mediated growth inhibitory effect in Hep3B cells. The progression of the cell cycle in eukaryotic cells is strictly controlled by the interaction of cyclins and Cdks with their inhibitory factors.…”
Section: Discussionsupporting
confidence: 89%
“…Because isorhamnetin-mediated cell cycle arrest at G2/M phase has been reported to be related to apoptosis in some cancer cell lines (Li et al 2014;Zhang et al 2015;Wu et al 2016;Wei et al 2018;Zhang et al 2018), it was evaluated whether G2/M arrest by isorhamnetin was associated with Figure 4. Effects of isorhamnetin (ISO) on the expression of Bcl-2 family proteins and cytochrome c, ROS generation and MMP in Hep3B cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its manufacturing process, the material composition of IN is about 10% organic and about 90% inorganic matter [6]. Its organic components are mainly indole alkaloids, such as indigo, indirubin [7], etc. The inorganic components contain more than 70% calcium carbonate and about 10% silica.…”
Section: Introductionmentioning
confidence: 99%
“…Cell membrane chromatography (CMC), developed by He and colleagues, represents a new type of biological affinity chromatography and is recognized as an effective method to screen bioactive components of complex systems (He & Geng, ; He et al ., ; Wang, Sun, Zhang, Du, & He, ). However, although CMC has been used to screen various components acting on various cells from complex systems (Chen et al ., ; Wu et al ., ), it still has the disadvantage of low sensitivity. Multiple techniques, like nuclear magnetic resonance spectroscopy (NMR) and gas or liquid chromatography mass spectrometry (GC–MS or LC–MS), have been used instead to analyze and identify unknown compounds, with LC–MS being the most widely used technique due to its high sensitivity, convenience and other advantages (Han, Zhang, Wei, & Wang, 2012; Han, Zhang, Huang, & Wang, 2012).…”
Section: Introductionmentioning
confidence: 99%